Online Coupling of Lab-on-Valve Format to Amperometry Based on Polyvinylpyrrolidone-Doped Carbon Paste Electrode and Its Application to the Analysis of Morin - Yang Wang; Guojun Yao; Jie Tang; Chun Yang; Qin Xu; Xiaoya Hu (Journal of Analytical Methods in Chemistry)
The potential capabilities and analytical performance of lab-on-valve (LOV) manifold as a front end to amperometry have been explored for the on-line determination of morin. Meanwhile, the electrochemical behaviors of morin were investigated based on polyvinylpyrrolidone- (PVP-) doped carbon paste electrode (CPE), which found that PVP can significantly improve its oxidation peak current. The excellent amperometric current response was achieved when the potential difference (ΔE) of 0.6 V was implemented in pH 6.5 phosphate buffer solution (PBS) that served as the supporting electrolyte. A well-defined oxidation peak has been obtained in studies using PVP as a modifier of CPE based on the oxidation of morin. The present work introduces the LOV technique as a useful tool for amperometric measurement, documents advantages of using programmable flow, and outlines means for miniaturization of assays on the basis of PVP modified CPE. The proposed method was applied successfully to the determination of morin in real samples, and the spiked recoveries were satisfactory.